2020
DOI: 10.1111/1440-1703.12151
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐shore distributions of peracarid crustaceans after changes in beach morphology: The importance of suction as a key geoenvironmental variable

Abstract: Recently, it has been shown that suction, which means the tension of moisture in sediments, is responsible for the distribution limits of the amphipods Haustorioides japonicus and Trinorchestia trinitatis and the isopod Excirolana chiltoni. Such effects take place through three distinctive suction‐induced mechanisms, associated with burrowing, physiology and the stability of burrows. Based on this background, in this study, we investigated storm‐induced morphological changes in beach profiles and the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…Because suction values dynamically changed along with the tidal changes (Yang et al 2019(Yang et al , 2020a, individuals of Haustorioides are thought to move their position to follow the zone of 0-2 kPa suction. Previous study also showed that H. japonicus kept their occurrence within the zone of 0-2 kPa suction both before and after storm induced morphological changes of sandy beaches (Yang et al 2020c). After storm induced beach morphological changes, it had been difficult to distinguish effects of passive movement of H. japonicus accompanied with sediment erosion and deposition on the beach or active movement following the spatial displacement of the zone of the specific suction (Yang et al 2020c).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Because suction values dynamically changed along with the tidal changes (Yang et al 2019(Yang et al , 2020a, individuals of Haustorioides are thought to move their position to follow the zone of 0-2 kPa suction. Previous study also showed that H. japonicus kept their occurrence within the zone of 0-2 kPa suction both before and after storm induced morphological changes of sandy beaches (Yang et al 2020c). After storm induced beach morphological changes, it had been difficult to distinguish effects of passive movement of H. japonicus accompanied with sediment erosion and deposition on the beach or active movement following the spatial displacement of the zone of the specific suction (Yang et al 2020c).…”
Section: Discussionmentioning
confidence: 75%
“…Previous study also showed that H. japonicus kept their occurrence within the zone of 0-2 kPa suction both before and after storm induced morphological changes of sandy beaches (Yang et al 2020c). After storm induced beach morphological changes, it had been difficult to distinguish effects of passive movement of H. japonicus accompanied with sediment erosion and deposition on the beach or active movement following the spatial displacement of the zone of the specific suction (Yang et al 2020c). Regarding the change of the vertical distribution of Haustorioides amphipods, the present results suggest the possibility of active movement of individuals selecting a preferable zone indicated by suction.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations